Topics on pediatric surgery. Teaching supporting aids for medicine students. - Zoe Quintero Delgado; Guillermo Cortiza Orbe; Carlos Cabrera Machado; Berta Fonseca Romero; Sergio Luis González López; Lorenzo Pérez Romano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
-